Entrepreneurship and development for a green resilient economy - Grigorescu, Adriana; Andrei, Jean Vasile (Emerald Publishing Limited, 2024)
The COVID-19 outbreak aggravated recurrent economic issues and problems of developing a resilient economy and technological development inequality between entities, countries, production structure, unemployment and social disorders that have resulted in the accentuating of political, economic, business and trade relations. Resilient economies, technological development and green entrepreneurship in the New Normal present opportunities and challenges in achieving a balanced transition. Entrepreneurship and Development for a Green Resilient Economy covers extensive ground in contemporary green entrepreneurship, from fundamental theories such as business investments and venturing capital to emerging and new concepts that reflect the critical challenges of the current times, including technological development slowdowns, economic resilience, economic systems downfalls, digitalization, green business footprints, and many more topics. Lab for Entrepreneurship and Development is Emerald's innovative book series on the study of entrepreneurship and development, striving to set the agenda for advancing research on entrepreneurship in the context of finance, economic development, innovation, and the society at large.
Keywords: Entrepreneurship.; Sustainable development.; Economic development -- Environmental aspects.; Business & Economics -- Entrepreneurship.; Entrepreneurship, Start-ups.; elektronické knihy; electronic books